Manajemen Strategik Pemasaran Perusahaan Jasa Alih Daya PT. Pelita Adhidaya Servindo - RA Kintania Zahra zahra; Rifa Rustikan rifa; Tri Wiyadi tri; Dinda Sekar Sari dinda (Publikasi Indonesia, 2022)
In this digital era, business between countries has entered the virtual network. The business climate is highly competitive in almost all sectors due to technological advances. To run a business people are required to manage the business in such a way as to be effective, efficient, and productive super- responsive and flexible to improve service to consumers. Taking into account the complexities of business management, the range of control of production processes and the availability of resources, encourages companies to invite other companies to partner in outsourcing format. By outsourcing a company submitssome of its production process to another company with the aim of obtaining one of the most efficient combination of resource use. In Indonesia the practice of outsourcing is actually not something new. The practice of handing over work to other companies has been known since Dutch colonial times. In Article 1601b of the Civil Code or Burgerlijk Wetboek (BW) it is found that there is a definition of chatering job . It is said that the Contract of Work, is an agreement between one party and another, where the one party (the employer of the work) wants a work which the other party can afford, on the payment of a certain money as the price of the contract.